2018
DOI: 10.1016/j.hbrcj.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of anchored sheet piles subjected to different types of sandy soils backfill

Abstract: A numerical parametric study using the finite element program of PLAXIS was performed on single and double anchored sheet piles systems using different types of sandy soil backfill (loose, medium dense, and dense sand). This numerical study aimed at evaluation of the variation of maximum values of bending moments and anchor forces exerted in the sheet piles. This evaluation was affected by varying of some parameters such as the embedded depth, positions of anchor rods either the upper rod or the lower one, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…18 and 19 show the upper anchor's forces are always less than the lower one through all the construction stages. Similar results can be seen in [20]. The total anchor's reactions forces do not follow a predictable behavior during the construction steps.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…18 and 19 show the upper anchor's forces are always less than the lower one through all the construction stages. Similar results can be seen in [20]. The total anchor's reactions forces do not follow a predictable behavior during the construction steps.…”
Section: Resultssupporting
confidence: 81%
“…The two results were convergent. Seleem [20] performed a 2D numerical parametric study to evaluate the variation of maximum values of bending moments and anchor forces exerted in the sheet piles. The study results indicated that the forces developed in the lower anchor rods are always higher than those developed in the upper anchor rods.…”
Section: Introductionmentioning
confidence: 99%
“…Figure (6) indicated that the maximum shear force decreases, as the anchor inclination increases, except when the angle of inclination is zero. The value of the maximum shear force when the angle of inclination equals to 10 degrees.…”
Section: Figure (5) the Relation Between The Maximum Bending Moment And The Anchor Inclinationmentioning
confidence: 95%
“…Design of anchored sheet pile wall depends on many factors like the height of excavation, surcharge loads, the kind of structure (temporary or permanent), and the level of groundwater table [3].The analysis and design of cantilever sheet pile walls and anchored sheet pile walls can be carried out utilizing a numerical model or traditional methods that depend on the limit equilibrium approach. Many researchers studied the safety conditions, soil deformation, lateral earth pressure distribution and stress-strain analysis for cantilever sheet pile walls and anchored sheet pile walls using the finite element method [4,5,6,7,8,9,10,11,12,13]. Tang et al [14] used a finite element model based on field data to investigate the lateral earth pressure distribution on sheet pile walls and provide the guidelines recommendations to design the sheet pile walls.…”
Section: Figure (1) Influence Of Ground Anchors On Wall Stability (After Sabatini Etal 1999)mentioning
confidence: 99%
“…A numerical parametric study using the finite element program of PLAXIS was performed on single and double anchored sheet piles systems for sandy [9]. This numerical study aimed at study the effect of varying of some parameters such as the embedded depth, and positions of anchor rods either the upper rod or the lower one.…”
Section: Introductionmentioning
confidence: 99%